Genetics of Melanoma - Torres-Cabala, Carlos A.; Curry, Jonathan L. (Cancer Genetics,, 2016)
This book discusses the molecular, biological, pathological, and clinical aspects of melanoma, with special emphasis in the new concepts of melanoma genetics. A multidisciplinary group of experts in Genetics, Dermatology, Pathology, and Melanoma Medical Oncology contribute state-of-the-art knowledge in melanoma research and clinical management, not only exposing the current status of knowledge of the topics but also providing their personal experiences and ideas about the future and potential practical application of the genetic aspects of melanoma. During the last few years we have witnessed an impressive amount of discoveries in the field of melanoma genetics which have changed our approach in understanding the pathogenesis and treatment of this lethal disease. Genetics of Melanoma is a practical approach to melanoma genetic mechanisms and their application in the diagnosis and treatment of this malignancy. It is an essential source of updated information and a powerful tool for clinicians, pathologists, and basic scientists who wish to understand, apply, and investigate the multiple new aspects of melanoma genetics.